(untitled) (Baghdad Science Journal, 2023)
An experimental investigation of the variation of argon discharge current with a glow and afterglow time intervals of a square discharge voltage was carried out at low pressure (6-11 mbar). The discharge was created between two circular metal electrodes of diameter (7.5 cm), separated horizontally by a distance (10 cm) at the two ends of a Pyrex cylindrical tube. A composite of two Gaussian functions has been suggested to fit and explain the variation graphs clearly. It is shown that the necessary times of glow and afterglow needed to attain a maximum discharge current are (70 us) and (60 us), respectively. The discharge current is observed to drop to the lowest value when the two times are serially longer than (85 us) and (72 us). Furthermore, the difference between the two times required to obtain a maximum rate of change in the discharge current, or a maximum discharge current, is deduced to be comparable to the breakdown time delay of gases reported in the literature. These observations can be useful for the design of plasma devices requiring specialized engineering.